Territoires et réseaux en Bretagne et Pays de la Loire à la fin de l'âge de Fer (IIIe-Ier siècles a.C.) - Rémy, Julie (Scripta Antiqua, 2021)
In the late Iron Age, the northwest of Gaul is divided into several independent cities. In the framework of this archaeological investigation, eight of them were studied between the Channel and the Atlantic coasts. Contrary to what researchers have long admitted, this synthesis, outcome of a doctoral thesis, highlights the full integration of these western regions into the social processes that mark the end of the Iron Age in Celtic Europe. These processes lead to the development of urbanism and the structuring of territories between the 3th and 1st centuries BC. The approach consists in analyzing the forms and functions of urban areas, but also in studying the religious spaces (sanctuaries), the hillforts and the aristocratic rural settlements. Nowadays, this extensive data compilation makes it possible to reason on the economic, even administrative, links existing between these various types of sites. Lastly, it allows you to reflect about the social structuring of the cities and the evolution of their organizations until the Early Roman Empire.